Myrtle-Functionalized Nanofibers Modulate Vaginal Cell Population Behavior While Counteracting Microbial Proliferation - Bellu, Emanuela; Diaz, Nicia; Kralovič, Martin; Divin, Radek; Sarais, Giorgia; Fadda, Angela; Satta, Rosanna; Montesu, Maria Antonia; Medici, Serenella; Brunetti, Antonio; Barcessat, Ana Rita Pinheiro; Jarošíková, Taťána; et al. (Plants (Basel, Switzerland), 2022)
Vaginal infections affect millions of women annually worldwide. Therapeutic options are limited, moreover drug-resistance increases the need to find novel antimicrobials for health promotion. Recently phytochemicals were re-discovered for medical treatment. Myrtle (Myrtus communis L.) plant extracts showed in vitro antioxidant, antiseptic and anti-inflammatory properties thanks to their bioactive compounds. The aim of the present study was to create novel nanodevices to deliver three natural extracts from leaves, seeds and fruit of myrtle, in vaginal milieu. We explored their effect on human cells (HeLa, Human Foreskin Fibroblast-1 line, and stem cells isolated from skin), resident microflora (Lactobacillus acidophilus) and on several vaginal pathogens (Trichomonas vaginalis, Escherichia coli, Staphylococcus aureus, Candida albicans, Candida kefyr, Candida glabrata, Candida parapsilosis, Candida krusei). Polycaprolactone-Gelatin nanofibers encapsulated with leaves extract and soaked with seed extracts exhibited a different capability in regard to counteracting microbial proliferation. Moreover, these nanodevices do not affect human cells and resident microflora viability. Results reveal that some of the tested nanofibers are interesting candidates for future vaginal infection treatments.
Keywords: health promoting; antimicrobial activity; bioactive compounds; myrtle; nanomaterials; cell behavior; vaginal infections; plant extracts